Food waste in campus dining operations: Inventory of pre- and post-consumer mass by food category, and estimation of embodied greenhouse gas emissions. Issue 3 (21st May 2015) - Costello, Christine; Birisci, Esma; McGarvey, Ronald G.
Abstract: There are many economic, social and environmental reasons to reduce the occurrence of food that is wasted. As communities consider options for managing their food waste streams, an understanding of the volume, composition and variability of these streams is needed to inform the decision-making process and potentially justify the capital investments needed for separation and treatment operations. This more detailed inventory also allows for the estimation of embodied resources in food that is wasted, demonstrated herein for greenhouse gas emissions (GHGs). Pre- and post-consumer food waste was collected from four all-you-care-to-eat Campus Dining Services (CDS) facilities at the University of Missouri, Columbia over 3 months in 2014. During the study period approximately 246.3 metric tons (t) of food reached the retail level at the four facilities. 232.4 t of this food was served and 13.9 t of it (10.1 t of edible and 3.8 t of inedible), was lost as pre-consumer waste. Over the same time period, an estimated 26.4 t of post-consumer food waste was generated at these facilities, 21.2 t of the waste edible and 5.3 t of it inedible. Overall, 5.6% of food reaching the retail level was lost at the pre-consumer stage and 10.7% was lost at the post-consumer stage. Out of the food categories examined, 'fruits and vegetables' constituted the largest source of food waste by weight, with grains as the second largest source of food waste by weight. GHGs embodied in edible food waste were calculated. Over the study period an estimated 11.1 t CO2 e (100-yr) were embodied in the pre-consumer food waste and 56.1 t were embodied in post-consumer food waste for a total of 67.2 t. The 'meat and protein' category represents the largest embodiment of GHG emissions in both the pre- and post-consumer categories despite ranking fourth in total weight. Beef represents the largest contribution to post-consumer GHG emissions embodied in food waste with an estimated 34.1 t CO2 e. This distinction between the greatest sources of food waste by weight and the greatest sources of GHG emissions is relevant when considering alternative management options for food waste.